Evaluation of Correlation between C-reactive Protein (CRP) Levels in Synovial Lavage Fluid and Clinical Staging of Temporomandibular Joint Internal Derangement Disorders by Diagnostic Arthroscopy: A Prospective Study - Mayank Singhal; Manoj Goyal; D.S. Gupta; Saurabh Bhardwaj (Journal of Orofacial Sciences)
Introduction: Pain in the temporomandibular joint (TMJ) is thecommonsymptom in the patients with TMD. Unfortunately, the factors mediating pain are not sufficiently known to permitspecific treatment. Therefore the knowledge about themediators and their specific effects on local inflammation and pain is very important. Material and Methods: seventy-two patients with the TMJ disorder based on the results of clinical and radiographic examination were examined and included in the study. Samples of lavage fluid were obtained prior to arthrocentesis by washing the joint with saline. Samples were assayed for CRP levels using Nycocard test (solid phase sandwich format immunometric assay), and concentrations were measured. Subjective pain was assessed by patients using a visual analog scale. Bone changes in the condyle were assessed by radiographs, and synovitis was assessed based on arthroscopic findings. Results: CRP was present in significantly higher concentrations in the synovial fluid of the TMJ, and the CRP levels were in significant correlation with clinical parameters as well as the arthroscopic findings in the patients. CRP levels (as per nycocard test) were 4.50 in patients suffering from Internal Derangement type II (SD ± 1.04) whereas in subjects with Internal Derangement type III it was 9.64 (SD ± 3.08), t-value 1.01. Conclusion: The CRP level in the TMJ synovial fluid significantly reflects the intensity of pain, or synovitis and the detection of high concentrations of the same is a possible marker of degradation in the TMJ.